Technological use of red jambo (Syzygium malaccense (L.) Merr. & L.M. Perry) in the production of ice cream (Research, Society and Development, 2023)
The red jambo (Syzygium malaccense (L.) Merr. & L.M. Perry) is a fruit characteristic of tropical regions, with high production in the north of Brazil, still neglected in terms of its commercial potential. It is a fruit with nutritional quality and bioactive compounds that make it a promising ingredient in the development of food products, such as ice cream. The use of fruits in the production of ice cream provides a higher quality product. The objective of the research was to develop a jambo ice cream by evaluating the physical, chemical, nutritional and sensorial properties. The formulation was established based on the standard basis for ice cream production. Analyzes of moisture, ash, carbohydrates, protein, fat, pH, titratable acidity, sensory evaluation and purchase intention were carried out. The ice cream obtained presented satisfactory results in terms of texture, creaminess, as well as good acceptance in the sensory evaluation, with the highest scores 8 and 9, especially for the flavor attribute. In this way, the use of red jambo in the production of ice cream can stimulate the expansion of the use of the fruit, both as an ingredient in the ice cream industry, as well as promoting income for local producers and serving as a basis for studies on the application of the fruit in other food products.